Self-Conception of The Vagrants in Jakarta - Rohim, Syaiful (Universitas Negeri Semarang, 2015)
This research aims to identify the self construction and communicating acts amongst the homeless while they are doing their daily activities as a vagrant in downtown Jakarta. The method being used for this research is a qualitative method with phenomenologist paradigm which aims to understand human behaviors from an experimental perspective. Result shows that vagrants, especially those who has the same profession, tend to share the area of work in order to avoid conflicts among them. Description from the subject in establishing communication with other vagrants are done by sharing area of expertise from himself and other vagrants. Results also showed that almost all the subjects tend to close their “darker” side from others who don’t know that they are vagrants by impression management. These people came into existence not only because of a poor culture which shows nomadic type of living habit, but it’s also because of the structure and vast majority which sees them with a negative stigma for every type of occupation they choose including a forced action because they were left without any choices other being a vagrant.